Performance Evaluation Of MPEG-4 Coded Video Transmission Over A Tetra Mobile Channel - Chang, Yoong Choon (2003)
TETRA (Terrestrial Trunked Radio) private Mobile Radio (PMR) was developed with support of European Telecommunications Standard Institute (ETSI) by the cooperation of manufacturers, users, and operators primarily to bring the benefits of standardisation to PMR. before this, every country in Europe had its own variant of PMR, based on its own signalling protocols, frequency allocation and regulatory framework. The TETRA standard supports communications of simultaneous voice and data. This brings significant benefits to both public safety and commercial users in that it enables a range of multimedia applications to be integarated with voice services.